1993
DOI: 10.1037/0021-9010.78.5.831
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of client abuse with locus of control and gender: A longitudinal study in mental retardation facilities.

Abstract: Direct-care workers (158 women and 154 men) participated in a study of aggressive work behavior. Employees completed J. B. Rotter's (1966) Locus of Control Scale. Client abuse data were collected over a 2-year period. Individuals reporting higher levels of external locus of control and men were more likely to emit aggressive behavior than were people reporting lower levels of external locus of control and women. Results supported the hypotheses and suggested that individual and group differences may be useful … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 19 publications
2
29
1
Order By: Relevance
“…Importantly, numerous studies document relationships between locus of control, behavior, and performance (Anderson, Hellriegel, & Slocum, 1977;Goodstadt & Hjelle, 1973;Kinicki & Vecchio, 1994;Mitchell, Smyser, & Weed, 1975;Perlow & Latham, 1993;Storms & Spector, 1987). Despite the apparent relationship between locus of causality and locus of control, we are aware of only one study that investigates the relationship between these two variables.…”
Section: Locus Of Controlmentioning
confidence: 92%
“…Importantly, numerous studies document relationships between locus of control, behavior, and performance (Anderson, Hellriegel, & Slocum, 1977;Goodstadt & Hjelle, 1973;Kinicki & Vecchio, 1994;Mitchell, Smyser, & Weed, 1975;Perlow & Latham, 1993;Storms & Spector, 1987). Despite the apparent relationship between locus of causality and locus of control, we are aware of only one study that investigates the relationship between these two variables.…”
Section: Locus Of Controlmentioning
confidence: 92%
“…With notable exceptions (e.g., Perlow & Latham, 1993;Skarlicki & Folger, 1997), studies of CWB have relied primarily upon single source self-reports. Attempts to demonstrate substantive relations among self-reported variables raise concerns such as shared biases that distort correlations among measures.…”
Section: Methodological Concerns With Self-report Studiesmentioning
confidence: 99%
“…Externals may be generally more aggressive in the workplace (Perlow and Latham, 1993), and are more likely to use coercive tactics in upward in¯uence than are internals (Lamude, Daniels and White, 1987). Goodstadt and Hjelle (1973) showed that individuals perceiving themselves as powerless who were given access to a range of in¯uence methods used coercive and punishing means of in¯uence far more often than individuals with an internal locus of control.…”
Section: Conditions Associated With Use Of a Hard Strategymentioning
confidence: 97%